Multifunctional bismuth ferrite nanocatalysts with optical and magnetic functions for ultrasound-enhanced tumor theranostics - Feng, Lili (2021)
Ultrasound (US)-assisted oncotherapy has aroused extensive attention due to its capacities to conquer significant restrictions covering short tissue penetration depth and high phototoxicity in photoinduced therapy. We herein developed a class of pure-phase perovskite-type bimetallic oxide, namely, bismuth ferrite nanocatalysts (BFO NCs), for multimodality imaging-guided and US-enhanced chemodynamic therapy (CDT) against malignant tumors. As-prepared BFO nanoparticles with poly(ethylene glycol)-grafted phosphorylated serine (pS-PEG) modification exhibit satisfactory physiological stability and biocompatibility. The BFO NCs also present high fluorescence emission within the second near-infrared region when irradiated with an 808 nm laser. Intriguingly, the BFO NCs demonstrate highly efficient US-enhanced generation of hydroxyl free radicals, as the cavitation bubbles produced by US trigger partial grievous turbulence and promote the transfer rate of the Fenton reagents. Thus, the BFO NCs enable effective inhibition of tumor growth assisted by external US, and the treatment efficacy can be monitored by computer tomography, magnetic resonance, and fluorescence imaging. Meanwhile, H2O2 and US, as a double logic gate, activate the BFO NCs to trigger the iron-catalyzed and US-enhanced CDT with high specificity and treatment efficiency. Therefore, the BFO NCs as a theranostic agent with an enhanced chemodynamic therapeutic effect assisted by external US and a multimodality imaging capacity are put forward, which show a promising prospect for noninvasive chemodynamic oncotherapy.